A study on motivation factors that would affect employee’s job satisfaction at Clay Industries Sdn Bhd / Nurul-Fateha Md Sandollah - Md Sandollah, Nurul-Fateha (2012)
Job satisfaction has been a matter of concern and attention in any field of business nowadays. Organizations realize that employee job satisfaction is the essential element to increase employee’s productivity. Employee’s dissatisfaction will lead to high absenteeism, poor performance and also give impact to organization output. Therefore, organization especially HR management must understanding what factor leads employee dissatisfaction and find the solution to overcome this problem. The dissatisfied employee complaints can be a useful source of information for the organization to develop motivation strategies to ensure that all employees are satisfied with their job. The past researcher shows that there are many factors of motivation that affect the employee’s job satisfaction. Therefore, this research study could be the tools that can increase employee’s job satisfaction .This study have been conducted at Clay Industries Sdn Bhd and it involved 300 respondents. In the final chapter, some recommendations were provided for future use to any researcher in this academic field.